Outlines of biochemistry / (Acc. 6387) - Conn, Eric E.. (New Delhi : John Wiley & Sons, 2016)
This book furnishes information about biochemistry and its varied applications. It is divided into three sections: Biological Compounds, such as proteins, nucleic acids, carbohydrates, lipids, and amino acids; Metabolism of Energy-Yielding Compounds, including comprehensive chapters on photosynthesis, the nitrogen and sulfur cycles, ammonia assimilation, and sulfate assimilation; and Metabolism of Informational Molecules, with chapters on molecular biology and biotechnology. Further more the text also features more information on plant biochemistry, a new chapter on genetic engineering, gene manipulation, and viruses and gene rearrangements.
Keywords: 1. Biochemistry